(untitled) (World Bulletin of Management and Law, 2023)
This article serves as a navigation guide for understanding the legal regulation of online advertising in the USA, EU and China, with a comparative analysis on key legislation, regulatory body and major principles. Author provides recommendations for the formulation of a legal framework governing online advertising in Uzbekistan, that would offer better protection to consumers in the context of online advertising, ensuring transparency, safety, and trust in the digital marketplace. Valuable insights and links for policymakers in the field, businesses, advertisers, foreign investors, consumers and students. #Law #Business #Advertising #Technologies #Trade #Ecommerce #ConsumerProtection #InternationalStandards #Uzbekistan